Perlindungan Hukum Terhadap Konsumen Akibat Keabsahan Perjanjian Proyek Meikarta - Angelina Dewi Permatasari; Larasati Rahmadhani; Lutfia Setiya Marsyalola; Muhammad Naufal Ramadhan; Dwi Desi Yayi Tarina (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The Meikarta project as the "Shenzhen of Indonesia", is an ambitious initiative by the Lippo Group to develop a large property project in Cikarang, Bekasi Regency, West Java. Although it offers various modern facilities, this project faces various obstacles, including construction delays and uncertainty about the fate of consumers who have made payments. This problem is further complicated by allegations of violations of the law related to building permits (IMB) and non-compliance with the Regional Spatial Plan (RTRW), as well as bribery cases involving local government officials. This study aims to examine the legal protection provided to consumers in relation to the validity of agreements made in the Meikarta project, with a focus on the legal implications of unlawful acts and legal uncertainty due to corruption cases. This study uses a qualitative method with a normative legal approach, which examines applicable legal provisions, and an empirical approach, which examines how the law is applied in practice, as well as data collection techniques through case studies and legal literature. The results of the study indicate that there is abuse in the validity of contracts that are detrimental to consumers, as well as the negative impact of legal uncertainty caused by corrupt practices. Legal protection for consumers, including lawsuits and government intervention, is essential to prevent further losses. It is hoped that this research will contribute to the formation of better legal policies and more effective consumer protection in Indonesia.